The Ethics Role of Good Governance in Indonesia - Anny Riwayati; Dwi Nur Handayani (ARRUS Journal of Social Sciences and Humanities, 2023)
The people trust the government to regulate the country. They hope that they will get prosper. The Government must always build this attitude of mutual trust at all times. The country will be divided and chaotic if the government breaks this trust. Reports in the media about corruption cases committed by State Officials are increasing. The increase in corruption cases committed by public officials is a slap. It shows that the state has unscrupulous bureaucrats. The ethics of every public official is an important factor in realizing good government. This study aims to determine whether the ethics of public officials can strengthen personal behavior by realizing a good government, especially in overcoming corruption. The method used in this study uses a qualitative approach, by conducting a descriptive analysis through a study of the collected literature. The results of the study show that the role of ethics is very important in forming bureaucrats that are free from corruption, collusion, and nepotism, and also to strengthen good governance.